Three-dimensional modal pushover analysis of buildings subjected to two components of ground motion, including its evaluation for tall buildings. - Reyes, Juan C. (Earthquake engineering & structural dynamics.)
The modal pushover analysis (MPA) procedure, presently restricted to one horizontal component of ground motion, is extended to three-dimensional analysis of buildings?symmetric or unsymmetric in plan?subjected to two horizontal components of ground motion, simultaneously. Also presented is a variant of this method, called the practical modal pushover analysis (PMPA) procedure, which estimates seismic demands directly from the earthquake response (or design) spectrum. Its accuracy in estimating seismic demands for very tall buildings is evaluated, demonstrating that for nonlinear systems this procedure is almost as accurate as the response spectrum analysis procedure is for linear systems. Thus, for practical applications, the PMPA procedure offers an attractive alternative whereby seismic demands can be estimated directly from the (elastic) design spectrum, thus avoiding the complications of selecting and scaling ground motions for nonlinear response history analysis.